THE PHILOSOPHY OF THE PRAXIS ACCORDING TO ADOLFO SÁNCHEZ VÁZQUEZ (Andamios, Revista de Investigación Social, 2006)
In Filosofía de la praxis, Adolfo Sánchez Vázquez interprets praxis (an obverse whose reverse is theory) as the main category of Marxism; he applies his abstractions to concrete history and he proposes along with Feuerbach that philosophy must not only interpret, but transform the world; he compares revolutionary and creative praxes with habitual practical activity; he finds its roots in work, and defines praxis as a teleological and utopian activity, that is to say, an ethical activity: based on the wish of wellbeing with and for others within fair institutions.
Keywords: Praxis; theory; historical particularization; teleology; and ethical evolution